Methane-specific gas detectors: the effect of natural gas composition - Hodgkinson, Jane; Pride, Russ D. (IOP Publishing, 2010)
Certain gas sensors, particularly those based on optical spectroscopy, have enabled the detection of individual gas species such as methane with low cross-sensitivity to other gases. For gas-specific instruments used to measure natural gas leaks, this paper considers whether it is necessary to consider the other components of natural gas in addition to methane. We have quantified the effect of gas compositional variation on methane-based measurements on the ppm, %LEL and %volume scales. %LEL measurements, important for safety applications, are the most challenging for methane-specific detection. Acceptable levels of error have been drawn from gas detector standards and by comparison with established gas detectors. The fundamental error expected from a methane-specific detector, as a result of variations in gas composition, would be larger than this benchmark on the %LEL scale. However for gas-specific detection, measurement of an additional component such as ethane is shown to reduce the error to below the benchmark level. This has been demonstrated experimentally using an instrument based on tunable diode laser spectroscopy.
Keywords: lower explosive limit lower flammable limit natural gas gas detection spectroscopy standards spectroscopy